VD_FINDINFO Pron / 2014 / 54 vom 4. September 2009 - VD Tribunal cantonal (2009)
AVOCAT, MODÉRATION, HONORAIRES CALCULÉS EN FONCTION DU RÉSULTAT POSITIF, DÉPENS | 45 al. 1 LPAv, 50 al. 1 LPAv, 50 al. 3 LPAv, 50 al. 4 LPAv, 48 LPA-VD, 55 LPA-VD